Peran BPSK (Badan Penyelesaian Sengketa Konsumen) Dalam Menyelesaikan Perkara Sengketa Konsumen (Studi Di Kabupaten Kuningan) - Fathanudien, Anthon; Dialog, Bias Lintang; Anugrah, Dikha (Fakultas Ilmu Sosial dan Humaniora, 2024)
The formation of BPSK was based on the tendency of people to be reluctant to go to court because the position of consumers was socially and financially unequal to business actors. The existence of BPSK is also expected to reduce the burden of cases in court. The first problem formulation is the role of BPSK in resolving consumer dispute cases and the second problem is the procedure and mechanism for resolving consumer disputes at BPSK. This research focuses on the Consumer Dispute Resolution Agency based in Kuningan Regency using a normative juridical type and approach. This research produces and concludes that the most important role of BPSK is handling consumer cases through mediation, conciliation and arbitration. The form of decision using the conciliation and mediation method is final and binding, without having to request a fiat of execution from the local District Court, while the form of decision adopted using the arbitration method must request a fiat of execution from the local District Court so that the arbitration award has executorial force.